An experimental study investigating the effects of bentonite clay on mechanical and thermal properties of concrete. (20th June 2023) - Gedik, Ebru; Atmaca, Adem
Highlights: The effects of BC on the mechanical and thermal properties of concrete was studied. The compressive strength of the samples with 5% BC is 94.7% higher compared to the control sample. The increased porosity of concrete with the use of bentonite mineral makes the heat transfer difficult. The thermal conductivity value of the samples with 5% BC is 31.22% lower compared to the control sample. Abstract: Concrete is one of the most popular building materials used in civil engineering applications. In order to reach the sustainability goals and produce more environmental construction materials, replacing some amount of cement in concrete with natural or industrial mineral additives is of great importance. In this research, from 0 to 30% by volume Portland cement (PC) CEM II 42.5R was replaced with bentonite clay (BC) and standard mortar samples were prepared in five different series, including control samples. Artificial aggregates (AA) with powder mixture of 90% ground granulated blast furnace slag (GGBFS) and 10% PC by weight were pelletized through cold-bonded agglomeration process in samples containing bentonite with different proportions. Mechanical tests and thermal conductivity tests have been performed on concrete samples at the age of 28 days. The results show that the compressive strength of the samples with 5% BC are 94.7% higher and the thermal conductivity of the same samples are 31.2% lower compared to the control sample. However, it is revealed that, increasing the amount of bentonite more than 15% decreases the mechanical and thermal properties considerably. The study revealed that the use of natural materials with low environmental impacts has increased the mechanical and thermal properties of construction materials which will provide significant benefits for sustainable construction.